Combine effect of bio-fertilizer and poultry manure on growth, nutrients uptake and microbial population associated with sesame (Sesamumindicum L) inNorth-eastern Nigeria - Samuel, Lihan; Rakiya, Abdullahi; Sheriff, Hewa H. (International Organization Of Scientific Research (IOSR), 2013)
The combine effect of bio-fertilizer (Azospirillum and arbuscularmycorrhiza fungi, AMF; Glomusmossea)and poultry manure (PM) on nutrients uptake, plant growth and soil microbial population associated with sesame under field condition was studied. The experiment comprised of four treatments; T1 (Azospirillum + AMF), T2 (Azospirillum + AMF + 5 ton ha-1 poultry manure), T3 (10 ton ha-1 poultry manure), and T0 (Control) laid out in randomized complete block design with three replications. Plant growth parameters viz., plant height, numbers of leaves/plant, numbers of branches/plant, leaf area, shoots and root dry biomass increased significantly due to the application of bio-fertilizer and poultry manure singly or in combination over control. Combined application of bio-fertilizer and poultry manure @ 5 ton ha-1 significantly produced the plants with desirable growth parameters, nutrients content and uptakes for N, P, and K. Root colonization by AM fungi was recorded in inoculated and un-inoculated plants. Colonization % ranges from 6% in control to 62.8% in Bio-organic. There was no significant difference in % root colonization of inoculated plants. Populations of Azospirillum and AM spores have increased in all treatments over the initial population prior to experiment in all treatments. Bio-organic recorded the highest Azospirillum population (28.56 × 10-6 CFU g-1 soil) and 69.3 AM spores g-1 soil and values were significantly higher to all the treatments. The overall findings of this research indicated that Bio-organic(bio-fertilizer and poultry manure @ 5 ton ha-1 ) produced plants with highest growth parameters, nutrients uptake, increased soil Azospirillum population, AM spore density and mycorrhization compared to exclusive application of bio-fertilizer or poultry manure @ 10 ton ha-1 .Combination of bio-fertilizer with organic amendments could be recommended for successful production of sesame.